Moderating effect of profitability: An analysis of factors that determine firm value in the Jakarta Islamic Indeks - Amri, Andi; Sagita, Ardio; Ramadhi, Ramadhi (Ekonomi Syariah IAIN Kudus, 2023)
The value of a firm is often examined by linking the factors that influence on its value. However, this method is no longer adequate because profitability also has a significant role in determining the value of a firm. Thus, incorporating the role of profitability in strengthening firm value is a necessary further step. This quantitative research uses samples of all JII companies within five years, from 2016 to 2020. Seventy financial statements were obtained as samples. Secondary data were obtained through the company website and www.idx.go.id. The analysis of data adopted was the Structural Equation Modelling (SEM) with the help of Smart PLS software. The findings show that the liquidity and debt policy have a positive and significant effect on firm value, but the capital structure, dividend policy, and profitability have no effect on firm value. Meanwhile, profitability has an effect as a moderator in the relationship between liquidity and debt policy on firm value. Nevertheless, profitability has no effect on the relationship between capital structure and dividend policy on firm value. This study could have practical implications whereby investors are more aware that stocks listed in the JII also have bright prospects in addition to their conventional counterparts.